P1.002 Development and Persistence of Anti-Chlamydial Antibodies in Women with Incident Chlamydia Trachomatis Infections in Uganda and Zimbabwe. (13th July 2013) - Gorwitz, R; Sereday, K; Pol, B Van der; Kwok, C; Morrison, C; Papp, J; Xu, F; Markowitz, L
Abstract : Background: Chlamydia trachomatis (Ct) IgG antibodies could provide evidence of past chlamydial infection for epidemiologic studies. Antibodies to chlamydial heat shock protein 60 (cHSP60) have been associated with complicated infection and infertility. Few studies have prospectively evaluated antibody development and persistence. Methods: Chlamydia serology (Medac IgG MOMP and cHSP60) was performed on stored sera from a cohort of 18–35 yr-old women seeking reproductive health services in Uganda and Zimbabwe who participated in a prospective study of HIV infection; study visits (including Ct-PCR testing) occurred on average every 80 days for up to 28 months. We analysed data on 135 women with ≥ 1 incident Ct infections who were IgG-seronegative prior to and had at least one IgG test on or after the date the incident infection was detected ("day zero"). Results: Sixty-six (49%) women seroconverted; of 54 tested on day zero, 46 (85%) were positive and 8 (15%) were negative and then positive when next tested (median 90 days). Of 12 seroconverters not tested on day zero, 11 (92%) were seropositive when next tested (median, 157 days). Nineteen (28%) of 69 non-seroconverters had no IgG testing beyond day zero and could not be assessed for delayed seroconversion. Of 52 seroconverters with subsequent testing, 27 (52%) remained persistently IgG-positive through the last test (median 248 days after seroconversion). Persistent IgG-positivity occurred in 61% (22/36) of those who were ever cHSP60-positive and 37% (6/16) of those who were not (NS), and in 56% (19/34) of those with only one Ct-PCR-positive visit and 50% (9/18) of those with more than one Ct-PCR-positive visit (NS). Conclusions: Anti-MOMP IgG antibodies developed in half of women with incident Ct infection and persisted in half of them. Although persistence was more common in those who were cHSP60-positive (suggesting complicated infection), the difference was not statistically significant.